2016
DOI: 10.18632/oncotarget.13971
|View full text |Cite
|
Sign up to set email alerts
|

Sodium fluoride (NaF) causes toxic effects on splenic development in mice

Abstract: At present, very limited studies focus on the toxic effect of sodium fluoride (NaF) on splenic development of human and animals in vivo. This study was firstly designed to evaluate the toxic effects of NaF on the splenic development of mice in vivo by observing histopathological lesions, changes of splenic growth index (GI), T and B cells, immunoglobulin A (IgA), immunoglobulin G (IgG) and immunoglobulin M (IgM) contents, cytokine protein expression levels, and cell cycle and cyclins/cdks protein expression le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…PCNA is an essential processivity factor for DNA polymerases, and it also is an index of cell proliferation [61]. Viscera index is usually used to assess the toxic effects of medicines and the development of living tissue [19,62]. In this study, the mRNA and protein expression levels of PCNA and the renal viscera index were reduced in the 24 and 48 mg/kg groups, suggesting that the proliferation of renal cells and development of the kidney were suppressed.…”
Section: Discussionmentioning
confidence: 63%
“…PCNA is an essential processivity factor for DNA polymerases, and it also is an index of cell proliferation [61]. Viscera index is usually used to assess the toxic effects of medicines and the development of living tissue [19,62]. In this study, the mRNA and protein expression levels of PCNA and the renal viscera index were reduced in the 24 and 48 mg/kg groups, suggesting that the proliferation of renal cells and development of the kidney were suppressed.…”
Section: Discussionmentioning
confidence: 63%
“…Several studies reported fluoride as an inducer of oxidative stress and modulator of intracellular redox homeostasis, lipid peroxidation, and protein carbonyl content [ 7 , 49 , 50 ]. These processes occur due to the ability to break hydrogen bonds in proteins (e.g., in the enzyme active center), as well as increasing the mitochondrial generation of free radicals resulting in oxidative stress, mitochondrial DNA degradation, and cell death [ 10 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, fluoride at lower concentrations ( μ M) acts as a stimulator and promotes cell proliferation, while at higher concentrations (mM), it inhibits enzyme action, including phosphatases [ 7 , 8 ]. In addition, high doses of ingested fluoride might damage several biological systems, including the central nervous system [ 9 ], reduction of splenic and humoral cell immunity [ 10 ], dysfunction of the male reproductive system [ 11 ], and liver damage [ 12 , 13 ]. Evidence in animal models suggests that fluoride concentrations above 5 mg/L in drinking water can modify cellular processes such as respiration and metabolism, thus leading to oxidative stress [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In different words, low concentration of fluoride (µM) might act as a promoter for cell proliferation and enzymatic activity; however, a high concentration of fluoride (mM) could act as an enzymatic inhibitor. This enzyme inhibitory action occurred due to the strong electronegativity of fluoride, where it forms ions and interacts with enzymes leading to toxicity and biological damage to different body systems [9], such as the central nervous system [10], spleen and immune organs [11], the male reproductive system [12], and the liver [13,14].…”
Section: Introductionmentioning
confidence: 99%